Analisis Jejak Karbon Dari Aktivitas Transportasi di Universitas Andalas - Yega Serlina; Fadhil Aditya Putra; Resti Ayu Lestari; Vera Surtia Bachtiar (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Increasing Green House Gases (GHG), including Carbon Dioxide (CO₂), have the potential to increase global temperatures, thereby causing climate change. Total CO₂ from human activities, for example transportation, electricity generation, industry, trade and agriculture, is expressed as a carbon footprint. Andalas University (Unand) has facilities that produce GHGs. This research aims to analyze the carbon footprint in Unand in the transportation sector. Samples were taken at the main gate (point 1) and back gate (point 2) Unand. For these two locations, the number of vehicles and fuel is calculated using the direct calculation method. The carbon footprint calculation refers to the Intergovernmental Panel on Climate Change (IPCC). The next step is to identify the potential for GHG reduction in Unand. The alternative GHG reduction observed is the absorption of CO₂ by vegetation. The research results show that the total carbon footprint on the Limau Manis Unand Campus is 2,221,020 kgCO₂eq/year from Point 1 and Point 2. The total CO₂ eq absorption capacity by vegetation on the Limau Manis Unand Campus is 9,297,557.51 kgCO₂ equivalent/year. When compared with the total CO₂ eq from transportation activities, the potential for reducing CO2 eq by vegetation is quite large. So, the Unand Campus road vegetation is still sufficient to reduce the 'contribution' of CO₂ eq from transportation activities in Unand to greenhouse gases. However, it is necessary to consider other possible sources of CO₂ besides transportation and the need to maintain existing vegetation